2014
DOI: 10.1186/1471-2164-15-841
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of protein palmitoylation in Caenorhabditis elegans

Abstract: BackgroundPalmitoylation is a reversible post-translational protein modification which involves the addition of palmitate to cysteine residues. Palmitoylation is catalysed by the DHHC family of palmitoyl-acyl transferases (PATs) and reversibility is conferred by palmitoyl-protein thioesterases (PPTs). Mutations in genes encoding both classes of enzymes are associated with human diseases, notably neurological disorders, underlining their importance. Despite the pivotal role of yeast studies in discovering PATs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…RNAi experiments were conducted using a previously described feeding protocol [ 53 ]. Worms were grown on HT115 (DE3) bacteria expressing pG-L4440-based plasmids from the C. elegans Open Reading Frame (ORF) RNAi feeding library (Source Bioscience, Nottingham, UK).…”
Section: Methodsmentioning
confidence: 99%
“…RNAi experiments were conducted using a previously described feeding protocol [ 53 ]. Worms were grown on HT115 (DE3) bacteria expressing pG-L4440-based plasmids from the C. elegans Open Reading Frame (ORF) RNAi feeding library (Source Bioscience, Nottingham, UK).…”
Section: Methodsmentioning
confidence: 99%
“…These studies indicated that DHHC sequence is critical for the PAT activity of Akr1 and Erf2, initially suggesting that DHHC family proteins are PATs. To date, a number of DHHC family proteins have been predicted in various species, including the yeast Saccharomyces cerevisiae (7 genes) [57], Caenorhabditis elegans (15 genes) [59], the fruit fly Drosophila (22 genes) [60], the mouse and human (23 genes) [9,32], and even the plant Arabidopsis (24 genes) [61,62]. Among these DHHC proteins, 6 (Akr1, Erf2, Swf1, Pfa3, Pfa4 and Pfa5) in yeast [47,52,57,[63][64][65][66], 20 (DHHC19, DHHC1121) in mammals [25,42,[67][68][69], and 2 (TIP1 and PAT10) in plants have already been confirmed as PATs [70,71].…”
Section: Enzymatic Activity Of Patsmentioning
confidence: 99%
“…The DHHC S-acyltransferase family in yeast is composed of five (Schizosaccharomyces pombe) to seven (Saccharomyces cerevisiae) members and this number goes up to 24 in mammals. Other model organisms such as Caenorhabditis elegans and Drosophila melanogaster also have about 20 predicted DHHC PATs (Bannan et al 2008;Edmonds and Morgan 2014;Fukata et al 2016). Whether all members of the family are expressed and functional in each organism remains to be established.…”
Section: Dhhc Protein S-acyltransferasesmentioning
confidence: 99%